Enantio- and diastereocontrolled total synthesis of (+)-boronolide - Kumar, P.; Naidu, S. V. (Journal of Organic Chemistry, 2006)
An efficient stereoselective total synthesis of (+)-boronolide from valeraldehyde is described. The key steps include a Sharpless asymmetric hydroxylation, a chelation-controlled vinyl Grignard reaction followed by a Sharpless asymmetric epoxidation, hydrolytic kinetic resolution, and a ring-closing metathesis.